Nucleostemin depletion induces post-G1 arrest apoptosis in chronic myelogenous leukemia K562 cells - Negin Gogani; Marveh Rahmati; Nosratollah Zarghami; Iraj Asvadi-Kermani; Mohammad Ali Hoseinpour-Feyzi; Mohammad Amin Moosavi (Tabriz University of Medical Sciences, 2014)
Abstract Purpose: Despite significant improvements in treatment of chronic myelogenous leukemia (CML), the emergence of leukemic stem cell (LSC) concept questioned efficacy of current therapeutical protocols. Remaining issue on CML includes finding and targeting of the key genes responsible for self-renewal and proliferation of LSCs. Nucleostemin (NS) is a new protein localized in the nucleolus of most stem cells and tumor cells which regulates their self-renewal and cell cycle progression. The aim of this study was to investigate effects of NS knocking down in K562 cell line as an in vitro model of CML. Methods: NS gene silencing was performed using a specific small interfering RNA (NS-siRNA). The gene expression level of NS was evaluated by RT-PCR. The viability and growth rate of K562 cells were determined by trypan blue exclusion test. Cell cycle distribution of the cells was analyzed by flow cytometry. Results: Our results showed that NS knocking down inhibited proliferation and viability of K562 cells in a time-dependent manner. Cell cycle studies revealed that NS depletion resulted in G1 cell cycle arrest at short times of transfection (24 h) followed with apoptosis at longer times (48 and 72 h), suggest that post-G1 arrest apoptosis is occurred in K562 cells. Conclusion: Overall, these results point to essential role of NS in K562 cells, thus, this gene might be considered as a promising target for treatment of CML.